Kesesuaian Kompensasi, Love of money, Whistleblowing system, Perilaku Tidak Etis dan Kecenderungan Kecurangan Akuntansi - Ni Komang Restu Murti Jeniari; Gayatri Gayatri (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This study aims to examine the effect of compensation suitability, love of money, whistleblowing system, and unethical behaviour on the tendency of accounting fraud. This research was conducted in 30 Village Financial Institution financial in Tabanan Regency by distributing questionnaires. Respondents used were 108 people. The data analysis technique used is multiple linear regression analysis. The results indicate that the love of money and unethical behavior have a positive effect on the tendency of accounting fraud, while the compensation suitability and the whistleblowing system has a negative effect. This means a high level of love for money and unethical behaviour can increase the occurrence of accounting fraud, but a high level of compensation suitability and the application of a good reporting system can minimize that.